The concomitant use of tyrosine kinase inhibitors and proton pump inhibitors: Prevalence, predictors, and impact on survival and discontinuation of therapy in older adults with cancer - Sharma, Manvi; Holmes, Holly M.; Mehta, Hemalkumar B.; Chen, Hua; Aparasu, Rajender R.; Shih, Ya‐Chen T.; Giordano, Sharon H.; Johnson, Michael L. (Cancer, 2019)
Background The concomitant use of tyrosine kinase inhibitors (TKIs) and proton pump inhibitors (PPIs) is a significant concern because of potential drug‐drug interaction that reduces TKI absorption, thus potentially reducing the effectiveness of TKIs. The objective of this study was to evaluate the prevalence and predictors of concomitant TKI‐PPI receipt and its impact on survival and therapy discontinuation in older adults with cancer. Methods This retrospective study used linked Surveillance, Epidemiology, and End Results‐Medicare data for the years 2007 through 2012. In total, 12,538 patients with lung cancer, renal cell cancer, chronic myelogenous leukemia, liver cancer, or pancreatic cancer were included. The primary exposure variable was concomitant receipt of TKI‐PPI, defined as at least 30 days of PPI use in the first 90 days from the start of the TKI (exposure period). The outcomes measured were overall survival and discontinuation of therapy in 90 days and 1 year after the end of the exposure period. Cox proportional‐hazards regression with inverse probability of treatment weighting was used to evaluate the association between exposure and outcome. Results The overall prevalence of TKI‐PPI receipt was 22.7%. Predictors that were associated with increased use included polypharmacy and prior PPI receipt. TKI‐PPI use decreased survival in 90 days (hazard ratio, 1.16; 95% confidence interval, 1.05‐1.28) and in 1 year (hazard ratio, 1.10; 95% confidence interval, 1.04‐1.18) but was not associated with discontinuation. Conclusions Nearly 1 in 4 older adults with cancer who receive TKIs also receive PPIs concomitantly, and concomitant use is associated with an increased risk of death. Concerted efforts to manage medications are needed to identify and reduce the receipt of PPIs when TKIs are initiated. Nearly 1 in 4 older adults with cancer concomitantly receive interacting tyrosine kinase inhibitors and proton pump inhibitors. The concomitant use of these drugs is associated with an increased risk of death.